“It doesn’t make any sense to even try”: the disruptive impact of COVID-19’s first wave on people with chronic pain using medical cannabis in New York - Yuval Zolotov; Jacinta Lomba; Megan Ghiroli; Mariya Masyukova; Julia H. Arnsten; Joanna L. Starrels; Jonathan Ross; Chinazo O. Cunningham; Deepika E. Slawek (Journal of Cannabis Research)
Abstract Background The COVID-19 pandemic disrupted health care but it is unknown how it impacted the lives of people using medical cannabis for chronic pain. Objective To understand the experiences of individuals from the Bronx, NY, who had chronic pain and were certified to use medical cannabis during the first wave of the COVID-19 pandemic. Methods We conducted 1:1 semi-structured qualitative telephone interviews from March through May 2020 with a convenience sample of 14 individuals enrolled in a longitudinal cohort study. We purposively recruited participants with both frequent and infrequent patterns of cannabis use. Interviews addressed the impact of the COVID-19 pandemic on daily life, symptoms, medical cannabis purchase, and use. We conducted a thematic analysis, with a codebook approach, to identify and describe prominent themes. Results Participants’ median age was 49 years, nine were female, four were Hispanic, four were non-Hispanic White, and four were non-Hispanic Black. We identified three themes: (1) disrupted access to health services, (2) disrupted access to medical cannabis due to the pandemic, and (3) mixed impact of chronic pain on social isolation and mental health. Due to increased barriers to health care in general and to medical cannabis specifically, participants reduced medical cannabis use, stopped use, or substituted medical cannabis with unregulated cannabis. Living with chronic pain both prepared participants for the pandemic and made the pandemic more difficult. Conclusion The COVID-19 pandemic amplified pre-existing challenges and barriers to care, including to medical cannabis, among people with chronic pain. Understanding pandemic-era barriers may inform policies in ongoing and future public health emergencies.